Research of function of Chinese synchronized swimming athletes on altitude training - Chen, C.; Cao, W. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The Chinese synchronized swimming team undertook altitude training on October 2003. During the one month training, players' physiological and biochemical indicator were tested in order to understand athletes' function, expand the domain of altitude training.